The Influence of Lecturer Service Quality, Family Support, Facilities and Infrastructure Availability, and Student Learning Motivation on Indonesian Nurse Competency Test Results - Andro Ruben Runtu; Fientje J.A. Oentoe; Herry Sumual; Beatrix J. Podung (Journal of Social Science, 2022)
The research analyzing the competency test for nurses is of particular concern for nursing education because incompetent nursing professions could not be registered as nurses in Indonesia. The purpose of this study was to determine the effect of lecturer service quality, family support, availability of learning facilities and infrastructure, and student learning motivation on the results of the Indonesian Nurses Competency Test (INCT). The research method used is quantitative research design with the Simple Random Sampling technique. The research sample was 100 respondents from the nursing profession graduates. Data collection by questionnaire, descriptive data analysis percentage, and regression test. The results of the study showed that there was an effect of the quality of lecturer services on the results of INCT (0.024), family support on the results of INCT (0.032), the availability of learning facilities and infrastructure on the results of INCT (0.015) and learning motivation on the results of INCT (0.030). Simultaneously, there is an effect of the quality of lecturer services, family support, availability of learning facilities and infrastructure, and learning motivation on the results of INCT (0.000), adjusted R¬Square test with a percentage of 77.1% of the variables of INCT results can be explained by the four variables. These results can be used as evaluations and policies for interested parties in improving the achievement of INCT graduation results, which are also a benchmark for implementing and quality assurance in higher education.